HYDROLOGICAL CHARACTERIZATION OF RAINFALL AND ITS POTENTIAL EROSIVITY IN THE MIDDLE COURSE OF SALITRE RIVER BASIN IN THE BRAZILIAN SEMI-ARID - Santos, Maria Ângela Cruz Macêdo dos (2021)
A characterization of the rains in the middle course of Salitre River Basin and its relation with the existing processes of water erosion is presented. Rainfall of 30 minutes was used to obtain the coefficient of disaggregation of rainfall. The annual maximum daily precipitation obtained from the National Water Agency database was adjusted according to the statistical distribution of Gumbel and the adjustment of the Kolmogorov-Smirnov adjustment. The individual erosive rains were established by the erosivity index (EI30) of each individual precipitation and kinetic energy were calculated according to Wischmeier and Smith, later compared to the methodology of Lombardi Neto and Moldenhauer. Higher precipitation intensities were observed for shorter run times and longer return periods. The highest rates of erosivity coincide with the highest rainfall indexes.